Quantitative validation of a proposed technical sustainability competency model: A PLS-SEM approach - Mukhtar, Nasiru; Kamin, Yusri Bin; Saud, Muhammad Sukri Bn (Frontiers in Sustainability, 2022)
The demand to enact sustainability into higher education so as to optimistically shape the wider society and biosphere has been stressed by UNESCO (2006). One of the approaches is through rethinking and revising education at all levels to capture obvious forms of present and imminent societies on the development of sustainability knowledge, skills, perspectives and values. Several HEIs have started to implement a number of facets to that effect, such as signing a climate commitment, working towards plan to make their campuses climate-neutral, and making sustainability their guiding principles and top priorities (Louw, 2013). However, Elder (2009) posited that analogous modifications to the curriculum are lagging behind. As a consequence, this study is set to quantitatively validate the technical sustainability competencies suitable for incorporation into Higher National Diploma electrical/electronic engineering curriculum in Nigeria. The authors used questionnaire to collect data from 168 respondents in the study area and consequently subject the data to descriptive and inferential statistics with the aid of PLS-SEM approach. The study discovered competencies suitable for incorporation into the curriculum. This includes cognitive skills in Eco-design and Life-Cycle Assessment; Research; Modeling, Simulation and Optimization; and Recycling/Renewable Resources. The study also found suitable psychomotor skills in Sustainable production, Use of modern engineering software tools, Operation/troubleshooting of electrical machines and devices, Communication/ICT, and waste-to-energy technology. Appropriate attitudes/values in Engineering ethics, Occupational safety and health, and Inter-generational equity were also discovered. This research is purely quantitative in nature carried out through administering questionnaires to respondents in one geo-political zone of the country. Thus, conclusions derived from these sources rely on the genuineness of the information provided by the participants. The findings offer accreditation body as well as curriculum developers in Nigerian polytechnics with a validated model of technical sustainability competences. This could be useful in the events of curriculum upgrade or renewal to integrate sustainability.